Delineation of groundwater potential zones (PGZs) using geospatial techniques and analytical hierarchy process (AHP), Kamrup metropolitan district, Assam - Parimita Saikia; Bijay Singh Mipun (National Geographical Journal of India, 2023)
Subsurface water refers to all water that exists naturally beneath the earth's surface. Groundwater is crucial for the formation of ecological niches, sustainability of the ecosystem, and socioeconomic development of a region. Groundwater accounts for 34% of the world's freshwater resources. The Kamrup Metropolitan District's rising population places a high demand on natural resources. One of them is groundwater. Unplanned rapid urbanisation accompanied by rising population growth led to significant anthropogenic changes to the environment of the region. Around 70% of the district's population is dependent on groundwater which has led to depletion. Therefore, the study of the potential groundwater zone is important to facilitate groundwater recharge through proper management. In GIS-Analytical Hierarchy Process (AHP) helps to evaluate the GWPZ. The study is based on assigning weights to eight interdependent factors that control groundwater potentials such as geomorphology, lineament density, elevation, slope, soil, drainage density, rainfall, and land use/land cover (LULC). These parameters were generated using remote sensing and conventional data. The study reveals that approximately 56% of the total area falls in the ‘good’ and ‘excellent’ potential zones. The remaining 44% of the region falls in the ‘poor’ and ‘fair’ categories.